Insulin glargine-based therapy improves glycemic control in patients with type 2 diabetes sub-optimally controlled on premixed insulin therapies - Davies, Melanie; Sinnassamy, Patrick; Storms, Fred; Gomis, Ramon (Diabetes research and clinical practice, 2008)
The AT.LANTUS trial recently demonstrated the efficacy and safety of insulin glargine initiation and maintenance using two different treatment algorithms in poorly controlled type 2 diabetes mellitus (T2DM). This sub-analysis investigated glycemic control and safety in 686 patients switching from premixed insulin (premix) with or without (±OADs) to once-daily glargine (±OADs/prandial insulin). A 24-week, multinational ( n = 59), multicenter ( n = 611), randomized study comparing two algorithms (Algorithm 1: clinic-driven titration; Algorithm 2: patient-driven titration) in four glargine ± OADs treatment groups: alone, once- (OD), twice- (BD) or >twice- (>BD) daily prandial insulin. After switching to the glargine regimen, HbA 1c levels significantly improved in the overall group (9.0 ± 1.3 to 8.0 ± 1.2%; p < 0.001) and in all subgroups; fasting blood glucose levels also improved in all subgroups (overall: 167.1 ± 50.0 to 106.9 ± 27.2 mg/dL [9.3 ± 2.8 to 5.9 ± 1.5 mmol/L]; p < 0.001). The incidence of severe hypoglycemia was also low in all four subgroups (≤1.7%). Patients with T2DM switching from premix ± OADs to glargine ± OADs had significant reductions in glycemic control with a low incidence of severe hypoglycemia. The addition of prandial (OD, BD or >BD) insulin was associated with further improvements in glycemic control. These data provide support for the stepwise introduction of prandial insulin to a more physiologic basal–bolus regimen, which is under investigation.